Feminicide in Cali Colombia: A view from public health - Benavides-Portilla, Mercedes-Isaura; Beitia-Cardona, Pedro-Nel; Estrada-Gonzalez, Catalina (Universidad y Salud, 2023)
Introduction: In most cases, violence against women is committed by their partners or ex-partners and this violence is a global public health problem that almost always ends in their death. Femicide is understood as the murder of a woman just for the fact of being a female individual, perpetuating gender inequality. Objective: To analyze femicide in Cali from its epidemiological characterization. Materials and methods: A descriptive population-based study was carried out using secondary sources that included 287 records of violent deaths of women. 53 cases between 2017 and 2019 were identified and analyzed, which were investigated and classified as femicide by the Crimes Against Women Unit of the Prosecutor’s Office. The epidemiological characterization was conducted based on the information provided, which was useful to identify the study variables: age, method, place of occurrence, imprisonment of perpetrator, and sentence. Results: Femicide occurred between the ages of 9 and 89, with stabbing being the most commonly used killing method. A conviction was executed only in 18.9% of the total cases. Conclusions: Femicide occurs at any age and has a high impunity degree mostly because of an ineffective judicial system.